Effect of APTMS modification on multiwall carbon nanotube reinforced epoxy nanocomposites. (1st April 2019) - Mishra, Kunal; Singh, Raman P.
Abstract: In this present investigation, we have studied the effect of chemical functionalization, and mechanical dispersion of carbon nanotube (CNT) reinforced epoxy resin. The chemical function of the CNT has been done by silane treatment. Silane modification has been done first by acid treatment on ball-milled CNT followed by chemical treatment of amine-based silane. FTIR spectra exhibit that silane chemically interacts with the CNT and epoxy resin. Mechanical dispersion of CNT in the epoxy was performed in the planetary ball mill. Ball milled CNT shows some degree of exfoliation. Mechanical properties of ball-milled and silane modified CNT reinforced epoxy is characterized in terms of fracture toughness and tensile modulus. Silane-modified CNT/epoxy shows an increase of 38% and 42% compared to the neat resin for fracture toughness and tensile modulus values respectively. Increase in the mechanical properties for silane modified CNT/epoxy is due to the excellent adhesion between CNT-matrix as well as significant dispersion of CNT in the epoxy resin provided by silane molecule as observed from TEM images. AFM indentation on the nanocomposites exhibits the presence of CNT agglomerates through adhesion and corresponding modulus map at the nanoscale level. SEM images indicate an increase in surface roughness with CNT inclusion which relates to the existence of an extrinsic mechanism. Additionally, better adhesion between CNT and matrix due to silane modification indicate a higher T g value of silane modified CNT/epoxy than ball milled CNT/epoxy.